1970
DOI: 10.1037/h0029303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orbital frontal lesions on aversive and aggressive behaviors in rhesus monkeys.

Abstract: Rhesus monkeys were tested for emotional reactions to human observers and to animal-like objects (doll and snake) before and after removal of orbital frontal (OF) or portions of temporal neocortex (T). The OF lesions, but not T lesions, initially produced hyporeactivity and anorexia, followed by hyperreactivity to environmental stimulation and heightened oral tendencies. The OF monkeys, unlike those with T lesions, showed increased frequencies of certain aversive reactions to the doll initially following surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
4

Year Published

1989
1989
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 234 publications
(83 citation statements)
references
References 17 publications
9
70
4
Order By: Relevance
“…We did not find a difference in the orbitofrontal cortical area between depressed patients with BPD and MDD without BPD in contrast to findings from both lesion (Butter et al, 1970;Grafman et al, 1996;Heinrichs, 1989;Raleigh et al, 1979) and neuroimaging studies (De La Fuente et al, 1997;Goyer et al, 1994;New et al, 2002New et al, , 2004Siever et al, 1999) that suggest a role for the orbitofrontal cortex in impulsive aggression. Our sample of depressed women with BPD did not differ significantly in terms of clinical measures of aggression and impulsivity from the depressed women without BPD (see Table 1).…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddcontrasting
confidence: 99%
See 1 more Smart Citation
“…We did not find a difference in the orbitofrontal cortical area between depressed patients with BPD and MDD without BPD in contrast to findings from both lesion (Butter et al, 1970;Grafman et al, 1996;Heinrichs, 1989;Raleigh et al, 1979) and neuroimaging studies (De La Fuente et al, 1997;Goyer et al, 1994;New et al, 2002New et al, , 2004Siever et al, 1999) that suggest a role for the orbitofrontal cortex in impulsive aggression. Our sample of depressed women with BPD did not differ significantly in terms of clinical measures of aggression and impulsivity from the depressed women without BPD (see Table 1).…”
Section: Orbitofrontal Cortex In Mdd With Bpd Compared To Mddcontrasting
confidence: 99%
“…Lesion studies suggest that control of aggression may be mediated by the anterior cingulate gyrus and orbitofrontal region (Butter et al, 1970;Grafman et al, 1996;Heinrichs, 1989;Raleigh et al, 1979). Functional neuroimaging studies of brain glucose metabolism in borderline and other aggressive and impulsive patients have also implicated the anterior cingulate area.…”
Section: Anterior Cingulate In Mdd With Bpd Compared To Mddmentioning
confidence: 99%
“…Our results contrast with previous reports (Butter et al, 1970;Butter and Snyder, 1972) in which monkeys with PFo damage were reported to show a decrease in aggression and an increase in avoidance behavior in response to human observers. These different results could be related to differences in the degree of familiarity of human observers or low interrater reliability for behavioral scoring (Butter et al, 1968(Butter et al, , 1970.…”
Section: Responses To a Human Intrudercontrasting
confidence: 56%
“…This set of findings is seemingly at odds with the evidence for functional interactions of the amygdala and the PFo in other settings (Baxter et al, 2000;Schoenbaum et al, 2003). To further complicate matters, yet other studies (Butter et al, 1970;Butter and Snyder, 1972) report an overall reduction in aggressive behaviors in monkeys with PFo lesions in the presence of a human observer and somewhat less of a reduction in aggression in response to a doll or snake.…”
Section: Introductioncontrasting
confidence: 45%
See 1 more Smart Citation